PERBANDINGAN EFEKTIVITAS OBAT KUMUR POVIDONE IODINE DENGAN KLORHEKSIDIN TERHADAP INDEKS PLAK - Novia Septiani Fauzia; Hanri Hartman; Jeffrey Jeffrey (Denta Journal Kedokteran Gigi, 2021)
Plaque is the main cause of the tooth and supporting tissues damage, so plaque control must be done. Chemical plaque control can be done by using mouthwash such as povidone iodine and chlorhexidine which is an effective antiseptics in reducing plaque formation. Both are proven to have antibacterial activity against Streptococcus mutans which is one of the plaque-causing bacteria. This research aims is to determine the difference of both mouthwash effectiveness to the plaque index. This research is pre-post test control group design by examining the plaque index before and after gargling. The subjects in this study are 32 students from SMPN 2 Cimahi who were 13 - 15 years old and were divided into two groups. This research was conducted by examining the plaque index before and after gargling using Silness and Loe plaque index. Data were tested for normality using Chi-square and analyzed by T-test. The results showed a difference average in plaque index before and after gargling with povidone iodine by 0.68 and chlorhexidine by 0.51 with a p-value of 0.11. Both mouthwash have almost the same effect on the plaque index.